Comparison of the Trend Moment and Naive Methods in Forecasting Gross Regional Domestic Product in Blitar Regency - Umi Habibah; Rizka Rizqi Robby; M. Nurhaqqul Qomaruddin (University of Mataram, 2022)
Gross Regional Domestic Product (GRDP) expenditure describes the final result of the production process within a region's territorial boundaries. Knowing GRDP expenses can describe the level of welfare economics, develop policy formulation, taxation, and export-import study. In estimating the GRDP of expenses in the following year, it is necessary to have a method of calculating systematically, one of which is forecasting. Some research showed that trend moment method and naive method produce higher accuracy than other methods. This method can be used in long-term forecasting and does not require the amount of data to be odd or even. The method is compared to get one of the best methods and has the highest accuracy value using MAPE calculation. The smaller MAPE, the better the forecasting accuracy. Comparing the two methods shows that the Naive method is the best method based on the MAPE criteria with an accuracy of 0.976 %. The result of data forecasting shows a decrease in GRDP Blitar Regency year 2021 and 2022.